Diagnostic or Therapeutic Strategies for Pregnancy Complications - Heazell, Alexander; Girard, Sylvie (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
It is well known that pregnancy complications, including preeclampsia, preterm birth, stillbirth, and intrauterine growth restriction affect over 12% of all pregnancies worldwide. These complications negatively impact both maternal and neonatal health and have short- and long-term effects such as an increased risk of neurodevelopmental and cardiovascular diseases. Over the past decade, numerous groups have investigated the use of new and/or existing drugs to either prolong gestation, such as in cases of threatened preterm labour; alleviate hypertension in preeclampsia; or promote adequate blood flow and nutrient delivery to the placenta to facilitate growth in IUGR. The overarching goal has been to promote healthier pregnancies and neonatal health, but it has been difficult to translate this work into the clinical setting, with problems in terms of drug delivery, specificity, and importantly, the early diagnostic capacities for complications in pregnancy. This book focuses on the early detection, potential novel therapeutic targets, risk factors, maternal outcomes, and long-term consequences of this critical problem.